Experimental Investigation and Modeling of Volume Shrinkage in Curing Epoxy Resins. Issue 1 (15th March 2018) - Leistner, Chris; Wittrock, Jörg; Abliz, Dilmurat; Ziegmann, Gerhard; Hartmann, Stefan
Abstract: The exothermic curing reaction of epoxy resins comes along with chemical shrinkage of the material. There do not exist established standard methods for determining the chemical shrinkage during the curing process. To this end, shrinkage measurements based on Archimedes' principle have been carried out for pure epoxy resin at different curing temperatures. In order to model the shrinkage behavior, these results can be related to the curing kinetics. For this purpose, additional DSC measurements have been carried out. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)